Thalassemia Screening in Reproductive-Age Groups at Unjani Campus - Rini Roslaeni; Susanti Ratunanda; Anita L Susanti; Towifah Fauziah Choerunisa; Prasetyo Notonegoro (Jurnal EduHealth, 2026)
Thalassemia screening is a crucial step in preventing the birth of infants with thalassemia major. Thalassemia major is a disorder that requires lifelong blood transfusions. Long-term transfusion therapy leads to iron accumulation in various organs, such as the heart, liver, and endocrine glands. Individuals with thalassemia major are born to parents who are both carriers of the thalassemia trait. Carriers do not exhibit any clinical symptoms; therefore, carrier status can usually only be identified through laboratory examinations. This community service activity aimed to increase awareness of early thalassemia detection through laboratory screening among unmarried individuals of reproductive age within the Unjani campus community. The approach employed was a community partnership involving students, lecturers, and administrative staff at Unjani. The examinations included complete blood count analysis and hemoglobin analysis. The activity was conducted from September to October 2025 at the Clinical Pathology Laboratory of the Faculty of Medicine, Unjani. A total of 246 participants were involved, of whom 7 were identified as thalassemia carriers, 1 was diagnosed with thalassemia major, and 2 were found to have Hb E thalassemia. Participants who were identified with thalassemia received special counseling regarding thalassemia screening among close family members and future spouses prior to marriage. Early detection of thalassemia is highly beneficial not only for current health awareness but also for preventing the transmission of genetic disorders to future generations.